Introduction to Waste Processing Technology to Address Organic Waste Issues in the Baru Beach Tourism Area - Syamsul Ma'arif; Ag. Eko Susetyo; Nurhadi, Nurhadi; M. Noviansyah Aridito; Esti Dwi Pujianingsih; Dinda Dwi Anggraeni; Nurul Istiqomah (PT FORMOSA CENDEKIA GLOBAL, 2023)
Community service activities are focused on increasing understanding of organic waste management in the Baru Beach Tourism Area. The main innovation lies in delivering lectures on various waste processing technologies, especially pyrolysis technology, to the participants, including Urban Village-Owned Enterprise BUMKal Mukti Lestari, Poncosari Urban Village, and residents around Baru Beach. Evaluation of activities using questionnaire data before and after the event. The analysis showed a significant increase in participants' understanding, although the peak understanding only reached 53%. Suggestions for increasing the effectiveness of subsequent activities include developing materials, extending time, and applying interactive methods. This community service activity increased public understanding of organic waste management in the Baru Beach Tourism Area.